Impact of social media marketing on consumer behavior: A comparative study of traditional marketing channels and digital platforms - Kumar Shetty, Harshith (BOHR International Journal of Advances in Management Research, 2024)
Today’s businesses are using social media marketing as a powerful method. It would help businesses to achieve their marketing goals in an effective way. It is possible by leveraging the power of various social media channels. Social Media Marketing utilizes social media platforms like Facebook, Instagram, WhatsApp, and Snapchat to advertise products and services. The main aim of social media marketing is to connect with existing customers and reach new customers. In social media marketing a number of strategies are involved. This comparative study examines the impact of social media marketing on consumer behaviour in comparison to traditional marketing channels. Through the analysis of data from both digital and traditional channels, the study highlights the significant impact of social media marketing on consumer behaviour. Digital platforms offer more benefits like interactive communication and customized content, which contribute to increased consumer engagement. The results of our study demonstrate the significance of utilizing social media marketing to enhance consumer engagement and satisfaction, presenting valuable insights to marketers in the current digital environment. A well-structured questionnaire was used to collect responses from 100 respondents in the Dakshina Kannada District of Karnataka State in this study. Our research revealed that customers are more inclined toward social media marketing than traditional marketing.